Disease monitoring using lung function trajectory in lymphangioleiomyomatosis: assessment in two national cohorts. Issue 1 (16th June 2022) - Johnson, Jan; Stewart, Iain; Johnson, Simon R
Abstract : Study question: In lymphangioleiomyomatosis, airflow obstruction and impairment of gas transfer progress at variable rates and serial lung function is recommended for disease monitoring. As these measurements are variable, recognising subjects needing treatment can be difficult. We used two prospective national cohorts to study change over time and variation in FEV1 to inform clinical decision making. Patients and methods: Clinical and lung function data for 141 UK and 148 American subjects were studied. Multilevel mixed effects modelling, route mean square analysis of errors and Bland-Altman analysis were used to analyse variability in lung function over time. Results: At baseline assessment, DLCO was reduced to a greater degree than FEV1 . In untreated patients, FEV1 and DLCO declined at proportionately similar rates independent of initial lung function. In mechanistic target of rapamycin (mTOR) inhibitor treated patients, FEV1 stabilised but DLCO continued to decline. FEV1 /DLCO per cent predicted ratio was 1.37 (0.43) at baseline and increased to 1.41 (0.50) after 42 (24) months (p=0.0002). At least five measurements were required before >70% of individuals had estimates of rate of FEV1 loss within 50 mL/year and DLCO loss within 0.1 mmol/min/kPa/year of the final values. Conclusions: While FEV1 and DLCO fall proportionately in most, in early disease and during mTOR inhibitor treatment, DLCO should also be monitored as it may fall independent of FEV1 . Since at least five observations over many months are required to make confident estimates of FEV1 and DLCO trajectories, new strategies are needed to measure disease activity and target early treatment appropriately.